Pervasive Development Disorder Reflected In Haruki Murakami's After Dark (2004): A Psychoanalytic Approach - Nuryanto, Fahmi Yahya, Dr. Phil. Dewi Chandraningrum, M. Ed, Titis Setyabudi, S.S. M. Hum (2015)
The major problem of this study is syndrome called pervasive development disorder. Because of frustration of life, they suffer syndrome pervasive development disorder as result they ignore about social interaction and socialization with the people around them. The objective of this study is to analyze Haruki Murakami's After Dark based on the structural elements and analyze this novel based on the Psychoanalytic Approach. The Writer employs qualitative method. The writer uses two data sources: primary and secondary. The primary data source is about the novel itself. Then, the secondary data sources are the books about psychoanalysis, references from internet about After Dark, and other sources, which are have relation to the analysis. The method of data collection is library research and the technique of data collection is descriptive technique. Based on the analysis, the writer get some conclusions. The study shows that the problem faced by the minor character is her own frustration and psychology condition. It is proved by her jealeous and frustation about daily activity as a famous person. This kind of syndrom may happen in almost teenager's mind in the beginning of process raising the age. The role of parents, religion, teachers, lectures and good society however is really important for teenager development.